Joint association between accelerometry-measured daily combination of time spent in physical activity, sedentary behaviour and sleep and all-cause mortality: a pooled analysis of six prospective cohorts using compositional analysis. Issue 22 (18th May 2021) - Chastin, Sebastien; McGregor, Duncan; Palarea-Albaladejo, Javier; Diaz, Keith M; Hagströmer, Maria; Hallal, Pedro Curi; van Hees, Vincent T; Hooker, Steven; Howard, Virginia J; Lee, I-Min; von Rosen, Philip; Sabia, Séverine; et al.
Abstract : Objective: To examine the joint associations of daily time spent in different intensities of physical activity, sedentary behaviour and sleep with all-cause mortality. Methods: Federated pooled analysis of six prospective cohorts with device-measured time spent in different intensities of physical activity, sedentary behaviour and sleep following a standardised compositional Cox regression analysis. Participants: 130 239 people from general population samples of adults (average age 54 years) from the UK, USA and Sweden. Main outcome: All-cause mortality (follow-up 4.3–14.5 years). Results: Studies using wrist and hip accelerometer provided statistically different results (I 2 =92.2%, Q-test p<0.001). There was no association between duration of sleep and all-cause mortality, HR=0.96 (95% CI 0.67 to 1.12). The proportion of time spent in moderate to vigorous physical activity was significantly associated with lower risk of all-cause mortality (HR=0.63 (95% CI 0.55 to 0.71) wrist; HR=0.93 (95% CI 0.87 to 0.98) hip). A significant association for the ratio of time spent in light physical activity and sedentary time was only found in hip accelerometer-based studies (HR=0.5, 95% CI 0.42 to 0.62). In studies based on hip accelerometer, the association between moderate to vigorous physical activity and mortality was modified by the balance of time spent in light physical activity and sedentary time. Conclusion: This federated analysis shows a joint dose–response association between the daily balance of time spent in physical activity of different intensities and sedentary behaviour with all-cause mortality, while sleep duration does not appear to be significant. The strongest association is with time spent in moderate to vigorous physical activity, but it is modified by the balance of time spent in light physical activity relative to sedentary behaviour.